Surface dislocation nucleation by wedge indenter contacts - Zhao, J; Ma, L; Korsunsky, A (2012)
Dislocation nucleation from a surface in contact with a rigid wedge indenter is studied in the framework of plane strain. First, the equivalent driving force on a singularity is derived in compact form. Using the result obtained, the driving force is then expressed in the form of complex integral formulae in terms of the Kolosov-Muskhelishvili potentials for wedge contacts. Then, by the Rice-Thomson model, a dislocation nucleation criterion is proposed for a surface loaded in contact, from which we obtain the critical contact size (equivalently, the critical contact load) and the dislocation emission angles at the different wedge indenter apex angles. Finally, the results are discussed, and conclusions are drawn. © 2012 Institute of Materials, Minerals and Mining.